Consumer credit : law and practice - Hill-Smith, Alexander G. L. (Milton Park, Abingdon, Oxon : Informa Law from Routledge, 2015)
'This book is a clear and complete guide to the new and complex legislation surrounding consumer credit and the problems that arise in the credit industry. In a thorough treatment of the subject, the author examines the terminology of the Acts involved, the agreements to which the regulations apply, withdrawal and cancellation, debtors' and creditors' rights, the provision of security, the powers of the court and enforcement provisions. The approach is extremely practical and designed specifically to support the needs of the practitioner. Fully updated for the second edition, the author covers the impact of Financial Services Act 2012 and the FCA regulations and enforcement powers which come into force in 2014. This comprehensive and practical guide is essential reading for legal practitioners, finance houses, credit reference agencies and retail organisations.'--
Key concepts in consumer credit law -- The regulatory framework -- Regulated activities and exempt agreements -- Authorisation and the failure to obtain it -- Continuing regulatory powers and obligations after authorisation -- Advertisement and financial promotion -- Pre-contract requirements -- Requirements governing entry into agreements -- Withdrawal and cancellation -- Rights of the borrower and hirer -- Rights and duties of the lender and owner -- The provision and regulation of security -- Regulated mortgage contracts : the mortgage and home finance : conduct of business sourcebook -- The conduct of particular types of credit activity -- Operation of ancillary credit activities -- Powers of the court : the financial ombudsman service.
Keywords: Consumer credit -- Law and legislation -- United Kingdom